Fosfato de arad, npk e calagem na cultura do milho em área de pastagem degradada - Teixeira, Pedro Emerson Gazel; Fernandes, Antonio Rodrigues; Galvão, Jessivaldo Rodrigues; Silva, Vicente Filho Alves; Melo, Nilvan Carvalho [UNESP] (My University, 2014)
The establishment of pastures in Amazonia is made to replace the woody vegetation by slash and burn process in chemically poor and low available phosphorus soils. The recovery of degraded areas is required and can contribute to reducing deforestation in the region. This study aimed to evaluate the effects of doses of Arad and NPK combinations in the management of maize in soil with low productive capacity. The experiment was conducted in Santo Antonio do Taua, Pará State, in an area with degraded pasture, in a dystrophic Oxisol. The experimental design was a randomized block split plot design with four replications. The plots were four phosphate: 50, 100, 200 and 300 kg ha-1 of P2O5 as Arad and sub-plots combination with NPK, NK, NK liming, and control (no match). We evaluated the growth characteristics and productivity of corn. Doses of Arad influenced the plant height and number of kernels per row cob. The application of Arad combined with NPK increased grain yield.
Phosphate arad npk and combined with lime in corn on pasture degraded
Keywords: Crop-livestock; Phosphate; Reactive phosphate; Soil correction; Zea mays L